1989
DOI: 10.1108/eb037660
|View full text |Cite
|
Sign up to set email alerts
|

Surface Mount Solder Joint Long‐term Reliability: Design, Testing, Prediction

Abstract: In this paper an overview of the issues underlying surface mount solder joint long‐term reliability is presented. The paper gives state‐of‐the‐art solutions for ‘Design for Reliability’ in simple design tool form, discusses the important accelerated reliability test issues, and provides the equations to estimate the reliability of SM product in use as well as the expected cyclic life in accelerated tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…3 and 4 previously) show clearly that the 84CTBGA outperforms the 192CABGA by a wide margin. 1,22,23 The 192CABGA package construction and very high die to package ratio generate higher shear strains in the solder joints resulting in earlier failures. This is demonstrated by the microscopic Moiré interferometry data in Fig.…”
Section: Effect Of Component Typementioning
confidence: 99%
See 1 more Smart Citation
“…3 and 4 previously) show clearly that the 84CTBGA outperforms the 192CABGA by a wide margin. 1,22,23 The 192CABGA package construction and very high die to package ratio generate higher shear strains in the solder joints resulting in earlier failures. This is demonstrated by the microscopic Moiré interferometry data in Fig.…”
Section: Effect Of Component Typementioning
confidence: 99%
“…Solder joint fatigue failures occur due to the coefficient of thermal expansion (CTE) mismatch between the component and the printed circuit board (PCB). 1 Although industry consortia had identified the Sn-Ag-Cu eutectic (nominally Sn3.8Ag0.7Cu) as the best option, the alloy that was used most widely in the first phase of implementation was the slightly hypoeutectic SAC305 alloy (Sn3.0Ag0.5Cu). SAC305 was endorsed by both the Japanese Electronics Industry Association (JEITA) and the IPC Solder Product Value Council (SPVC).…”
Section: Introductionmentioning
confidence: 99%
“…The Englemaier-Wild solder creep-fatigue equation [154][155][156][157][158][159][160][161][162][163] relates the cyclic total strain energy, to the median cyclic fatigue life for both isothermal-mechanical and thermal cycling:…”
Section: Fatigue Life Predictionmentioning
confidence: 99%
“…Depiction of the Effects of the Accumulating Fatigue Damage[32] Fatigue test results are obtained by cycling smooth or notched specimens until failure, and are presented in a form of S-N diagram (where S is the stress amplitude, and N the number of cycles to failure) as shown inFigure 1.10. Since the 1950s, researchers have developed several models to predict the number of cycles to failure of solder materials including the Engelmaier-Wild equation [32], Palmgren-Miner linear damage law, Coffin-Manson relation [33], etc.…”
mentioning
confidence: 99%
“…Although well studied, a board level joint scale reliability study of Ag micro-alloyed Sn58Bi solder joints produced with SMT has not been reported and this is essential to assess its viability as a SnPb replacement. The combination of thermal fatigue and solder joint creep is considered to be a predominant failure mechanism of electronic assemblies, and it is of particular interest to end users requiring high reliability [30]. ATC is a widely used reliability evaluation technique that simultaneously produces static and strain-induced microstructural evolution in solders as a result of thermal expansion mismatch, thereby accelerating fatigue and creep damage mechanisms [10,12,[31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%